Epiregulin promotes the migration and chemotaxis ability of adipose‐derived mesenchymal stem cells via mitogen‐activated protein kinase signaling pathways. Issue 10 (16th July 2018) - Cao, Yangyang; Wang, Liping; Yang, Haoqing; Lin, Xiao; Li, Guoqing; Han, Nannan; Du, Juan; Fan, Zhipeng
Abstract: To investigate the function of epiregulin (EREG) in the migration and chemotaxis ability of mesenchymal stem cells. Adipose‐derived stem cells (ADSCs) were used in this investigation. Lentiviral EREG short hairpin RNA was applied to silence EREG expression in ADSCs. Human recombinant EREG protein (rhEREG) was used to perform a gain‐of‐function study. Scratch‐simulated wound migration and transwell chemotaxis assays were used to examine the migration and chemotaxis capacity of ADSCs in vitro. Using a Western blot assay, the expressions of p38 mitogen‐activated protein kinase (p38 MAPK), c‐Jun N‐terminal kinase (JNK), extracellular signal‐regulated protein kinases 1 and 2 (Erk1/2), and protein kinase B were detected. Depletion of EREG caused by specific short hairpin RNA restrained the migration and chemotaxis ability of ADSCs and inhibited the expressions of phosphorylated p38 MAPK, JNK, and Erk1/2. rhEREG improved ADSCs migration and chemotaxis capacity, which was repressed by knockdown of EREG and rescued the expressions of phosphorylated p38 MAPK, JNK, and Erk1/2 impaired by silencing EREG. Furthermore, rhEREG‐improved migration and chemotaxis ability in EREG‐depleted‐ADSCs was restricted by a specific inhibitor, SB203580, for blocking p38 MAPK signaling, PD98059 for blocking Erk1/2 signaling, or SP600125 for blocking JNK signaling in ADSCs separately. EREG promotes migration and chemotaxis ability of ADSCs through MAPK signaling pathways. Abstract : Epiregulin promotes the migration and chemotaxis ability of adipose‐derived stem cells through mitogen‐activated protein kinase signaling pathways.